A new optimization strategy for wind/diesel/battery hybrid energy system. (15th January 2022) - Aziz, Ali Saleh; Tajuddin, Mohammad Faridun Naim; Hussain, Moaid K.; Adzman, Mohd Rafi; Ghazali, Nur Hafizah; Ramli, Makbul A.M.; Khalil Zidane, Tekai Eddine
Abstract: HOMER software is a powerful tool for modeling and optimization of hybrid energy system (HES). The main two default control strategies in HOMER are load following (LF) and cycle charging (CC) strategies. In these strategies, the decision to use the generator or battery at each time step is made based on the lowest-cost choice. Therefore, these strategies are difficult to be implemented in practice especially in countries with continuous fuel price fluctuations. In this study, a new dispatch strategy based on HOMER-MATLAB Link Controller for an isolated wind/diesel/battery HES is proposed to overcome the limitations of the default HOMER strategies. A detailed technical, economic, and greenhouse gas emission analysis is presented for the system under LF, CC, and the proposed dispatch strategies. Besides offering more realistic optimization, the results show that the proposed strategy offers the best economic and environmental performance with a net present cost of $56473 and annual CO2 emissions of 6838 kg. Furthermore, the sensitivity analysis reveals that the proposed strategy is not affected by the fuel price variation, in opposite to LF, and CC strategies which is affected dramatically by this variation. The findings are of paramount importance towards more realistic and efficient energy management strategies. Highlights: A new dispatch strategy for wind/diesel/battery hybrid energy systems using HOMER-MATLAB Link Controller is proposed. Overcome HOMER default strategies limitation in dealing with continuous fuel price fluctuations. The proposed strategy is compared with HOMER default strategies in terms of techno-economic and environmental performance. Sensitivity analysis is conducted by considering variations in critical parameters. The proposed strategy is more realistic and has better economic and environmental performance than HOMER default strategies.